Disseminated tuberculosis and tuberculous meningitis in Australian-born children; Case reports and review of current epidemiology and management - Smith, B.; Hazelton, B.; Heywood, A.; Snelling, Thomas; Peacock, K.; Macartney, K. (Wiley-Blackwell Publishing Ltd., 2013)
We present two cases of tuberculous meningitis in Australian-born children. We review the current literature surrounding management of paediatric tuberculosis and disseminated disease, emphasising the importance of prompt diagnosis and intervention. We discuss the epidemiology of tuberculosis in the Australian paediatric population and highlight the sentinel role of childhood infection in public health surveillance. © 2012 The Authors. Journal of Paediatrics and Child Health © 2012 Paediatrics and Child Health Division (Royal Australasian College of Physicians).